An Analysis of the Technological Structure of Refineries and Blenders : Estimation of the Leontief Multiproduct Cost Function and Reservation Prices - Domínguez, Juan Manuel (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2015)
The Leontief multiproduct flexible cost function aims to give an approach to the technology used by refineries and blenders. In general, this cost function satisfies rational behavior restrictions imposed by economic theory. The estimated marginal costs are incorporated in a monopolistic competition model to calculate the virtual prices of other products provided by refineries and blenders in the hypothetical situation in which reformulated gasoline is absent in fuel markets. I have found that conventional gasoline and other product prices are greater than those in the mentioned hypothetical case. This result reflects the fact that consumers are being charged with high prices in order to have available a fuel which satisfies the Environmental Protection Agency (EPA) regulations. Finally, when all the products become perfect substitutes, i.e. consumers are not interested in the quality of fuels, price differences tend to be negligibly small.